2016
DOI: 10.1080/10245332.2016.1240391
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher disease epidemiology and natural history: a comprehensive review of the literature

Abstract: Signs and symptoms of GD frequently mimic more common hematologic conditions resulting in missed or delayed diagnosis. Early diagnosis and prompt initiation of treatment when indicated is crucial to prevent or minimize life-altering or life-threatening liver and skeletal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
129
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(138 citation statements)
references
References 62 publications
0
129
0
9
Order By: Relevance
“…A recent review of the literature found that the worldwide incidence ranged from 0.39–5.80 per 100,000 with a prevalence of 1.33–1.75 per 100,000, although the data available is quite limited [16]. The carrier frequency for a glucocerebrosidase gene mutation is estimated at 0.0343 in the Ashkenazi Jewish population, and 0.006 in the general population [10,16]. The majority of patients have type 1 GD, the main type seen in the Ashkenazi Jewish population.…”
Section: Epidemiologymentioning
confidence: 99%
“…A recent review of the literature found that the worldwide incidence ranged from 0.39–5.80 per 100,000 with a prevalence of 1.33–1.75 per 100,000, although the data available is quite limited [16]. The carrier frequency for a glucocerebrosidase gene mutation is estimated at 0.0343 in the Ashkenazi Jewish population, and 0.006 in the general population [10,16]. The majority of patients have type 1 GD, the main type seen in the Ashkenazi Jewish population.…”
Section: Epidemiologymentioning
confidence: 99%
“…With the increased use of ERT over time, symptomatic patients began to receive treatment at younger ages and less severe stages of presentation.ERTremains the gold standard for treatment of gauchersdisease [10].ERT is indicated for patients with type 1 Gauchers disease who manifest with clinical signs and symptoms like anemia, thrombocytopenia , organomegaly and spleenomegaly . Early diagnosis and prompt initiation of treatment when indicated is crucial to prevent or minimize life altering or life threateningliver and skeletal complications [11]. Enzyme replacement therapy seems to eliminate the need for DOI: 10.9790/0853-160303107110 www.iosrjournals.org 110 | Page bone marrow transplantation and has favourable effects on symptoms and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Gaucher disease is a rare, autosomal recessive condition caused by bi‐allelic pathogenic variants in the β‐glucocerebrosidase gene ( GBA ; Nalysnyk, Rotella, Simeone, Hamed, & Weinreb, ). GBA encodes the protein glucocerebrosidase (GBA), which hydrolyzes glucosylceramide into ceramide and glucose (Balestrino & Schapira, ).…”
Section: Introductionmentioning
confidence: 99%